IMPROVING STUDENTS’ VOCABULARY MASTERY BY USING WORD MATCHING TECHNIQUE OF THE SEVENTH GRADE AT SMP TD PARDEDE FOUNDATION - Epiana Banjarnahor; Maria Marpaung; Sarah Siburian; Pingky Ayu Sitorus; Rahma Wati (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2020)
AbstractVocabulay is an important language center to be mastered by students in learning English. The lackof mastery of English vocabulary by seventh grade students in the SMP TD PARDEDE FOUNDATION is the researchers goal to find a technique that can be used in improving students’ vocabulary. This research applied classroom action research through Word Matching Technique. Word Matching Technique is a technique that can be used in increasing students’ vocabulary and with applying Word Matching Technique the students can be more interested, active, and enthusiastic in giving a good responsein learning vocabulary. This research used two cycles. The researche data were collected by using some instruments, namely vocabulary tests, observation sheet, questionnaire sheet, and diary notes. In the Test I, Test II, and Test III have increased. The mean of Test I (Cycle I) was 54,8. Test II (Cycle I) was 66,4. And Test III (Cycle II) was 92,2. The results of the questionnaire, observation, and diary notes showed that the implementation of Word Matching Technique helped the students to improve their vocabulary mastery and could motivate them to learn  English.Keywords : Class Action Research, Vocabulary, Word Matching TechniqueAbstrakKosakata adalah pusat bahasa yang penting untuk dikuasai oleh siswa dalam mempelajari bahasa inggris. Kurangnya penguasaan kosakata bahasa inggris oleh siswa kelas tujuh di SMP TD PARDEDE FOUNDATION menjadi tujuan peneliti untuk menemukan suatu teknik yang dapat digunakan dalam peningkatan kosakata siswa. Penelitian ini menerapkan penelitian tindakan kelas melalui teknik pencocokan kata. Teknik pencocokan kata adalah sebuah teknik yang dapat digunakan dalam meningkatkan kosakata siswa dan dengan menerapkan teknik pencocokan kata siswa dapat lebih tertarik, aktif, dan antusias dalam memberikan respon yang baik dalam belajar kosakata. Penelitan ini menggunakan dua siklus. Data penelitian dikumpulkan dengan menggunakan beberapa instrument, yaitu tes kosakata, observasi, kuisioner, dan catatan buku harian. Pada Tes I, Tes II, dan Tes III mengalami peningkatan. Nilai rata-rata Tes I (Siklus I) adalah 54,8, Tes II (Siklus I) adalah 66,4, dan Tes III (Siklus II) adalah 92,2. Hasil dari kuisioner, observasi, dan catatan buku harian menunjukkan bahwa penerapan Word Matching Technique membantu siswa meningkatkan penguasaan kosakata dan dapat memotivasi mereka untuk belajar bahasa inggris.Kata kunci : Penelitian Tindakan Kelas, Kosakata , Word Matching Technique